Lo político, la política y el acontecimiento - Ema López, José Enrique (Foro Interno, 2007)
This paper proposes a categorization of political action that entails three key elements. The first involves the tension between politics and the political sphere, and deals with the conflictive tendency of practices and logics that seek to establish an order in contrast with others that seek to undermine it. The second element refers to changes in the borders that define the sphere of that which is social-naturalized and that which is political-controversial. The third element, the political event, refers to the moment of political production in which these two extremes are simultaneously intertwined and subverted. Finally, we offer some implications of the recognition of the “impossibility of fullness” as an essential aspect of all that is political, including politics itself.